The frozen elephant trunk technique in acute aortic dissection: the ultimate solution? An institutional experience - Wisniewski, K.; Dell’Aquila, A. M.; Motekallemi, A.; Oberhuber, A.; Schäfers, J. F.; Marchiori, E.; Weber, R.; Martens, S.; Rukosujew, A. (Frontiers in Cardiovascular Medicine, 2024)
Objective: Acute aortic dissection remains a serious emergency in cardiovascular medicine and the challenge for cardiothoracic surgeons. In the present study, we sought to compare outcomes of different surgical techniques for the repair of type A acute aortic dissection. Methods: From April 2015 to May 2023 - 213 patients (82 women, aged: 63.9 ± 13.3 years) with acute aortic dissection (205 type A and 8 non-A-non-B dissections) underwent surgical treatment in our department. 45 patients were with the Frozen Elephant Trunk (FET) technique supported by the Thoraflex™ Hybrid prosthesis, 33 received Total Aortic Arch Replacement (TAR) - standard or Conventional Elephant Trunk, and 135 were treated with Hemiarch Replacement (HR). The aortic arch surgery was performed in most cases under moderate hypothermic (28°C on average) circulatory arrest with selective antegrade cerebral perfusion through right axillary artery. Results: Early mortality was 17.8% (38 perioperative deaths) in the whole population, 8.9% by FET- group, 33% and 17% in TAR and HR patients, respectively (P value 0.025). Rate of spinal cord injury was 2.3% (5pts.), paresis of recurrent laryngeal occurred in 3.7% of cases (7pts., 4 of them were treated with FET). Permanent neurological dysfunction occurred in 27 cases (12.7%). After a mean follow-up of 3 years, mid-term mortality of discharged patients was 19.4% (34 deaths - 7 FET, 4 TAR and 23 HR) and the overall mortality was 33.8% (72 deaths: 11 FET – 24.4%; 15 TAR. – 45.4%; 46 HR – 34.1%). 8 FET patients (17.8%) received additional endovascular treatment in the descending aorta. Conclusions: In our institutional experience, the frozen elephant trunk technique using high-end Thoraflex Hybrid prothesis emerges its surgical suitability in treatment of acute aortic dissection with favorable outcomes. FET technique and our perioperative management lead to comparable neurological outcomes and superior mortality rates in these urgent cases.